Effects of Urban Configuration on Human Thermal Conditions in a Typical Tropical African Coastal City - Emmanuel Lubango Ndetto; Andreas Matzarakis (Advances in Meteorology)
A long-term simulation of urban climate was done using the easily available long-term meteorological data from a nearby synoptic station in a tropical coastal city of Dar es Salaam, Tanzania. The study aimed at determining the effects of buildings’ height and street orientations on human thermal conditions at pedestrian level. The urban configuration was represented by a typical urban street and a small urban park near the seaside. The simulations were conducted in the microscale applied climate model of RayMan, and results were interpreted in terms of the thermal comfort parameters of mean radiant (Tmrt) and physiologically equivalent (PET) temperatures. PET values, high as 34°C, are observed to prevail during the afternoons especially in the east-west oriented streets, and buildings’ height of 5 m has less effect on the thermal comfort. The optimal reduction of Tmrt and PET values for pedestrians was observed on the nearly north-south reoriented streets and with increased buildings’ height especially close to 100 m. Likewise, buildings close to the park enhance comfort conditions in the park through additional shadow. The study provides design implications and management of open spaces like urban parks in cities for the sake of improving thermal comfort conditions for pedestrians.